ChemInform Abstract: Interpenetration of a 3D Icosahedral M@Ni12 (M: Al, Ga) Framework with Porphyrin‐Reminiscent Boron Layers in MNi9B8. Issue 8 (February 2016) - Zheng, Qiang; Wagner, Frank R.; Ormeci, Alim; Prots, Yurii; Burkhardt, Ulrich; Schmidt, Marcus; Schnelle, Walter; Grin, Yuri; Leithe‐Jasper, Andreas
Abstract: The new borides AlNi9 B8 (I) and GaNi9 B8 (II) are prepared by arc melting of the elements with a 5% excess of Ga for loss compensation followed by annealing (alumina crucibles in evacuated quartz tubes, 920 °C (I) or 895 °C (II), 7 d).